Survey of highly pathogenic (H5N1) avian influenza virus among fighting cocks and human contacts, Sa Kaeo Province, Thailand, 2014 - ศรีจารนัย สมยศ; โสภี ยุทธนา; ศรีมงคล ยุทธพงษ์; โห้วงศ์ ดารารัตน์; ทองเล็ก สมเกียรติ; คำนึง ประวิทย์; รัตนมังคลานนท์ สมชวน; จิตตกานต์พิชย์ มาลินี; พิริยะพรพิพัฒน์ สุขุม (Disease Control Journal, 2014)
Background: In 2013, 27 human cases of Influenza A (H5N1) were reported from Cambodia. Sa Kaeo shares its land border with Cambodia. We conducted a study in Sa Kaeo Province to survey of H5N1 avian influenza virus among fighting cocks and human contacts, to identify factors associated with viral infection and to recommend strategies for prevention and control of disease transmission between humans and animals. Methods: In 2014, a cluster survey of 735 fighting cocks and 47 Thai adult contacts were enrolled in cross-sectional survey and prospective cohort study of zoonotic transmission. (1) a survey using structured questionnaire to interview our volunteers to collect data on history of illness and routine activities and keep contacted weekly for 3 months by phone to identify acute influenza-like illnesses (ILI) (2) laboratory screening were assessed in human by using serological and oropharyngeal swab techniques in both groups looking for evidence of H5N1 infection. During December 1, 2013 - February 28, 2014. A seropositive result was defined as an influenza H5N1 neutralizing antibody titer of > 1:80. Results: All specimens from poultry were negative by the isolation and propagation in embryonated chicken eggs and also 47 participants were report negative H5N1 serological results. Fifteen ILI cases (31.90%) were identified as influenza B (3) Influenza A (2) Parainfluenza (1) and Adenovirus virus (1) infections by real-time RT-PCR. Conclusions: avian-to-human transmission of influenza H5N1 virus was not found in Sa Kaeo Province. Development of influenza surveillance among fighting cocks and proper management of the viral transmission was recommended.